Integrating Corporate Zakat and Corporate Waqf: A Synergistic Model for Sustainable Islamic Philanthropy - Fadhilah, Selva Nur; Efendi, Nur; Nurhasanah, Neneng (Journal of Comprehensive Science, 2025)
Zakat and waqf are the main instruments of Islamic social finance with complementary functions: zakat plays a role as a short-term distribution, while waqf supports sustainable development through productive assets. This research aims to formulate the conceptual foundation for zakat-waqf integration of corporations, develop short-term and long-term synergy models, establish principles of governance and impact measurement, and offer an implementation map in Indonesia's Islamic philanthropic ecosystem. Using a comparative case study method on Rumah Zakat and Sinergi Foundation, the results show a complementary continuum model where zakat serves as seed capital for emergency needs and initial empowerment, while waqf ensures the sustainability of socio-economic benefits. In conclusion, the integration of corporate zakat and corporate waqf has the potential to strengthen the accountability, sustainability, and effectiveness of Islamic philanthropy while supporting maq??id al-syar?'ah and the Sustainable Development Goals (SDGs).